FRI0547 Magnetic Resonance Imaging Joint Space Narrowing Is An Independent Predictor of Radiographic and MRI Damage Progression in Patients with Early Rheumatoid Arthritis. (15th July 2016) - Møller-Bisgaard, S.; Ejbjerg, B.; Eshed, I.; Hørslev-Petersen, K.; Hetland, M.; Jurik, A.G.; Thomsen, H.; Torfing, T.; Stengaard-Pedersen, K.; Junker, P.; Krogh, N.S.; Lottenburger, T.; et al.
Abstract : Background: Magnetic Resonance Imaging (MRI) osteitis and synovitis have been identified as predictors of structural damage progression in rheumatoid arthritis (RA) 1, 2, but the predictive value of MRI joint space narrowing (JSN, a measure of cartilage damage) and tenosynovitis (TS) needs further investigation. Objectives: To investigate the predictive value of baseline MRI inflammatory and damage parameters on 2 year MRI and X-ray damage progression in an early RA (eRA) cohort following a non biologic treat-to-target strategy. Methods: In 129 eRA (<6months) patients from the double-blind randomized CIMESTRA trial (methotrexate, intraarticular betamethasone and cyclosporine (CYA)/placebo CYA) contrast-enhanced MRIs of the non-dominant wrist and X-rays of hands and feet were performed at baseline and after 2 years. MRIs were evaluated according to the RAMRIS scoring system for osteitis, synovitis, erosion (ES), JSN, for TS 3 and X-rays according to the Sharp/van der Heijde method, with known chronology by two experienced radiologists. Potential predictive baseline variables (MRI osteitis, synovitis, TS, ES, JSN, X-ray ES and JSN, DAS28, gender, age, anti-CCP, smoking status) were tested in univariate linear regression analyses with 2-year change in MRI total damage score, Total Sharp Score (TSS), and MRI and X-ray JSN and ES scores as dependent variables. Significant variables (p<0.05) were included in multiple regression analyses with backward selection. Results: Independent predictors of structural damage progression are presented in table 1 . If MRI JSN was not included in the model, MRI osteitis score was statistically significant independent predictor of X-ray progression (coefficient 0.32, p=0.001, vs TSS progression). Conclusions: This trial is the first to report that MRI JSN independently predicts both X-ray and MRI damage progression in early RA. Further studies are needed to confirm early MRI-determined cartilage damage as predictor of progressive joint destruction in RA. References: Hetland et al, Ann Rheum Dis 2009 Boyesen et al, Ann Rheum Dis 2011 Haavardsholm et al, Ann Rheum Dis 2007 Disclosure of Interest: None declared